Cultural Integration in Tafsir al-Iklil fi Ma’ani al-Tanzil by Misbah Mustafa within the Context of Javanese Islam - Supriyanto; Islah Gusmian; Zaenal Muttaqin (UIN Sunan Kalijaga Yogyakarta, 2024)
This study examines Tafsir al-Iklil fi Ma’ani al-Tanzil by Misbah Mustafa in the context of shaping Javanese Islamic identity. Previous research has often overlooked the specific relationship between Qur'anic interpretation and the local socio-cultural dynamics of Javanese society. To address this gap, this study analyzes how Tafsir al-Iklil serves as a bridge, integrating Islamic teachings with Javanese cultural traditions. Using a qualitative approach through literature review, the primary data is sourced from Tafsir al-Iklil, supported by secondary literature. The analysis involves data selection, reduction, and interpretation, employing historical and hermeneutical approaches. The findings reveal that Misbah Mustafa’s exegesis provides a unique perspective on the development of Javanese Islam, emphasizing its integrative nature, where religious teachings harmonize with Javanese cultural practices. Misbah highlights responsive spiritual leadership and social responsibility in religious rituals, suggesting that Javanese traditions hold spiritual values that align with Islamic teachings. This study contributes to the academic discourse by demonstrating how Qur'anic exegesis plays a pivotal role in merging religious doctrines with cultural traditions, broadening the understanding of Javanese Islamic identity through a textual lens. The integrative typology that emerges from this exegesis portrays Islam in Java as more than a formal religion—it is a comprehensive way of life, encompassing social, economic, and cultural dimensions.